2010
DOI: 10.1590/s0100-06832010000600011
|View full text |Cite
|
Sign up to set email alerts
|

Inoculação da soja com Bradyrhizobium no sulco de semeadura alternativamente à inoculação de sementes

Abstract: RESUMOA fixação biológica de N é indispensável à soja no Brasil, dispensando o uso de N mineral e reduzindo o custo de produção. O objetivo deste estudo foi comparar a inoculação da soja com Bradyrhizobium no sulco de semeadura com a inoculação tradicional nas sementes, em solo com baixo teor de matéria orgânica e desprovido de bactérias nodulantes dessa cultura. Foi conduzido um experimento de campo no cerrado de Roraima no ano de 2006 e repetido nas mesmas condições em 2007, sendo avaliados os tratamentos: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 6 publications
(11 reference statements)
1
11
1
9
Order By: Relevance
“…Negative effects have also been observed in the BNF in the associated use of B. japonicum with fungicides. Bueno et al (2003) and Zilli et al (2010b) tested the effect of fungicides on survival and nodulation of B. japonicum and obtained a reduction of microorga-nisms in combinations of fungicides carboxim+thiram. Moreover, Marks et al (2013) found that the use of cell additive in combination with inoculant and specifically Maxim fungicidal seed treatment of soybean improved survival and longevity of B. japonicum in the seed, and maximized BNF technology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Negative effects have also been observed in the BNF in the associated use of B. japonicum with fungicides. Bueno et al (2003) and Zilli et al (2010b) tested the effect of fungicides on survival and nodulation of B. japonicum and obtained a reduction of microorga-nisms in combinations of fungicides carboxim+thiram. Moreover, Marks et al (2013) found that the use of cell additive in combination with inoculant and specifically Maxim fungicidal seed treatment of soybean improved survival and longevity of B. japonicum in the seed, and maximized BNF technology.…”
Section: Resultsmentioning
confidence: 99%
“…Seeing that the beneficial effects of using insecticides and fungicides for seed treatment is imminent, it is necessary to continue studies to find the ideal setting for inoculation which really identifies the time, since reduction of inoculation may occur to effectuate it in the same instant that the fungicide and insecticide are used. Therefore, recent research shows physiological and yield performance with in-furrow inoculation has been useful alternative for soybean, because it does not use seed treated with fungicides, decreases nodulation (Zilli et al, 2010b) with fungicides/insecticides, does not interfere with on leaf N and yield. Although there is observed green stem and leaf retention in soybean, similarly it uses seed without anything in the sow (Favero and Lana, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the bacterial BNF efficiency depends on various edaphoclimatic factors, especially in the tropical regions. Moreover, management practices such as treatment with fungicides prior to inoculation also interfere in the bacterial BNF efficiency (Hungria, Campo & Mendes, 2007;Campo, Araújo, Mostasso & Hungria, 2010;Zilli, Gianluppi, Campo, Rouws & Hungria, 2010;Hungria & Mendes, 2015).…”
Section: Introductionmentioning
confidence: 99%